Women Farmers in Timor-Leste : Bridging the Gender Gap in Agricultural Productivity - Gavalyugova, Dimitria (World Bank, Washington, DC, 2019)
Agriculture is the predominant economic activity in Timor-Leste, with more than 80 percent of households engaged in at least minor farming work, with 70 percent of farmers over the age of 401. Despite its leading role in the livelihoods of Timorese households, the agricultural sector has not fulfilled its potential and cereal yields in Timor-Leste are among the lowest in the East Asia and the Pacific (EAP) region. This is a direct barrier in the country’s efforts to achieve its National Development Strategy and the 2030 Agenda for Sustainable Development.